A COMPARATIVE ANALYSIS OF AMERICAN AND BRITISH ENGLISH (Наука и инновации, 2026)
English is a global language with multiple standardized varieties, among which American English and British English are the most influential. This study provides a detailed comparative analysis of these two varieties. The research examines differences in vocabulary, spelling, grammar, pronunciation, punctuation, and usage conventions. The findings reveal systematic and historically grounded differences shaped by sociocultural and political factors. The study concludes that neither variety is inherently superior; both represent equally valid forms of English in global communication.